Urgensi Pesero Komanditer Memberi Persetujuan kepada Pesero Pengurus dalam Melakukan Tindakan Kepemilikan - Florensya Octavia Tanriawan; Nurini Aprilianda; Hariyanto Susilo (Jurnal USM Law Review)
This study aims to explore and analyze the urgency of the approval of limited liability companies in ownership actions carried out by management partners in limited liability companies. The urgency of this research lies in developing an understanding of the role and protection of the rights of limited partners in safeguarding their interests and investments. The research method used is normative legal research with statutory and conceptual approaches. The results of the study show the urgency of the approval of limited partnership partners with managing partners in the act of ownership is essential to protect the rights and interests of limited partners, with effective legal protection, written agreements, and good communication between parties to avoid disputes and ensure the sustainability of the company. The novelty of the research lies in an in-depth analysis of the legal protection for limited liability companies and the impact of own actions without the approval of limited partners, which provides a more comprehensive understanding of the importance of limited partnership approval in the legal and business context so that this research is expected to open deeper insights into the mechanisms and legal implications of acceptance given by limited partners as a form of protection for investors and financial conditions in limited liability companies.